2012
DOI: 10.1210/me.2011-1282
|View full text |Cite
|
Sign up to set email alerts
|

Antiapoptotic Signaling via MCL1 Confers Resistance to Caspase-3-Mediated Apoptotic Cell Death in the Pregnant Human Uterine Myocyte

Abstract: Our group has previously identified elevated levels of nonapoptotic active caspase 3 (CASP3) accompanied by increased prosurvival, antiapoptotic signaling in the pregnant mouse uterus during late gestation. We speculated that increased antiapoptotic signaling desensitized the pregnant uterine myocyte to the apoptotic action of uterine CASP3. This current study examines the mechanism by which the pregnant myocyte gains resistance to the apoptotic effects of increased uterine CASP3. Using both primary human preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Mouse kidney cells from P4 and each of eight cell lines subcloned from them at P17 were observed during establishment and proliferation at progressive tissue culture passages; Figure 2A illustrates changes in expression of survival–associated proteins from P4 to P22 of the +/+ and -/- kidney cells. The +/+ kidney cells lose expression of Fhit gradually with passage, show increasing Survivin expression and steady Mcl1 to P22 [ 21 , 22 ], two modulators of apoptosis. This alteration of Fhit expression levels in +/+ cells may be due to epigenetic modifications, since we have not detected allelic losses at the fragile Fra14a2 locus within the murine Fhit gene ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…Mouse kidney cells from P4 and each of eight cell lines subcloned from them at P17 were observed during establishment and proliferation at progressive tissue culture passages; Figure 2A illustrates changes in expression of survival–associated proteins from P4 to P22 of the +/+ and -/- kidney cells. The +/+ kidney cells lose expression of Fhit gradually with passage, show increasing Survivin expression and steady Mcl1 to P22 [ 21 , 22 ], two modulators of apoptosis. This alteration of Fhit expression levels in +/+ cells may be due to epigenetic modifications, since we have not detected allelic losses at the fragile Fra14a2 locus within the murine Fhit gene ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…The supernatant was retained as the nuclear fraction. Our previous published data in the human myometrial cell [21] and in this current study of the pregnant mouse uterus, has revealed that the uterine cytoplasmic fraction (containing cytosol, membranes and subcellular organelles (excluding the nucleus)) displays stable levels of protein disulfide isomerase (PDI) across gestation and the nuclear levels of the nuclear receptor co-activator 3 (NCOA3) remain relative constant across gestation in the pregnant mouse uterus relative to subcellular protein concentrations. We have therefore utilized NCOA3 and PDI to ensure equal loading for immunoblotting and as markers to determine the purity of the isolated nuclear and cytoplasmic protein fractions, respectively.…”
Section: Methodsmentioning
confidence: 64%
“…Utilizing the mouse as our model system, we have also identified increased levels of active CASP3 at mid gestation, which decline as term approaches in a progesterone (P4) regulated manner through direct targeting of the uterine contractile architecture [2]. We also observed a gestationally regulated anti-apoptotic signaling cascade that permits the pregnant uterus to maintain a non-apoptotic phenotype despite elevated uterine CASP3 activity [3], [4].…”
Section: Introductionmentioning
confidence: 78%
“…CASP3 activity is commonly associated with the initiation of cellular apoptosis 21 . However it has repeatedly been demonstrated that despite high levels of active CASP3, the pregnant myometrium avoids cellular apoptosis throughout the entirety of gestation and postpartum involution, whereas the endometrium displays increased apoptotic CASP3 activity at term and during the involution process 22 , 23 . While CASP3 targets were not identified in the smooth muscle of the bladder, CASP3 was found to target structure proteins in both the heart and diaphragm.…”
Section: Discussionmentioning
confidence: 99%